2011
DOI: 10.3109/14767058.2011.596960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implementing family-centered rounds (FCRs) in a neonatal intensive care unit (NICU)

Abstract: FCR was associated with enhanced collaboration among team members for NNPs and fellows. Parents' satisfaction scores increased post FCR on survey items regarding communication. Since NNPs and fellows are the primary communicators with parents, the increased satisfaction may reflect improved communication due to FCR. This added opportunity for open dialogue may also contribute to the increased parent satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 23 publications
2
68
1
1
Order By: Relevance
“…15 FCRs improve parental satisfaction, communication, and collaboration between fellows and nurse practitioners in the neonatal intensive care unit. 16 Consistent with these findings, residents in our study reported improved parental satisfaction secondary to enhanced communication and information sharing, resulting in improved parental understanding of their child's condition and better comprehension of providers' roles. Patient satisfaction is a critical outcome measure, and FCRs may be a powerful venue for future physicians to learn effective communication and information sharing.…”
Section: Fcrs Patient Satisfaction and Communicationsupporting
confidence: 78%
“…15 FCRs improve parental satisfaction, communication, and collaboration between fellows and nurse practitioners in the neonatal intensive care unit. 16 Consistent with these findings, residents in our study reported improved parental satisfaction secondary to enhanced communication and information sharing, resulting in improved parental understanding of their child's condition and better comprehension of providers' roles. Patient satisfaction is a critical outcome measure, and FCRs may be a powerful venue for future physicians to learn effective communication and information sharing.…”
Section: Fcrs Patient Satisfaction and Communicationsupporting
confidence: 78%
“…Parents who spend more time with their infants have more opportunities for perceiving the signs of infants' discomfort and their other needs; consequently, they function better in comparison with nurses who are responsible for the care of multiple infants. [18] Parental satisfaction in a single-family room NICU was higher in comparison with the traditional open-bay NICU system. The single-family room environment seemed more conducive to the provision of FCC.…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment and reinforcement 4,5,15,17,21,22 Obstacle High expectation of family 9,10,13 Negative opinion of medical staff 9,10,13,20 Strategy Leadership 14 Participation of family 17,19 Continuing support from staff 14,17,19,22 Communication Description Improving communication 3,10,15,18 Consideration for family 10,18,21 Sharing care plan 3,15,21 Obstacle Language barrier 4,7,11,15,19 Poor understanding 10,11,15,17 Handing out bad news 9,12 Strategy Using easy words 4,6,15,22 Interpreter training 19 Mediative participation of nurse 1,16,25 Understanding of culture …”
Section: 가족과 의료진의 협력mentioning
confidence: 99%
“…Rosen et al 21 Descriptive study 27 patients, 53 staff members Physician, senior resident, intern, medical student, nurses, care coordinator, social worker, and pharmacist, patient, family or legal guardian…”
Section: Nonementioning
confidence: 99%